Перспективы развития бизнеса в условиях глобализации - Поповский, А.С. (Культура народов Причерноморья, 2002)
So as Ukraine not to change into adjunct of industrialized countries in the presence of proper advanced technologies, ukranians exporters can be use as a guide global marketing, which create a basis for forming ukranian transnational companies.